Barriers and Facilitators to Intake of Dairy Products in Adolescent Males and Females With Different Levels of Habitual Intake. (17th March 2017) - Racey, Megan; Bransfield, Jeanette; Capello, Kathryn; Field, David; Kulak, Verena; Machmueller, David; Preyde, Michèle; Newton, Genevieve
Background: Dairy products and alternatives can contribute to overall good health including positive body composition and decreased adiposity; however, these foods are grossly underconsumed by youth, and worldwide, almost 25% of children are overweight or obese.Objective: The study investigated the barriers and facilitators toward dairy consumption by Grade 7 youth.Methods: Thirty 50-minute, audio-recorded focus groups were conducted with 134 students in eight Grade 7 classes across 5 elementary schools. Focus groups were led by trained facilitators in the elementary schools and participants were separated based on dairy consumption and gender. Recorded data were transcribed and thematically analyzed using qualitative analysis software to identify themes related to barriers and facilitators to dairy product intake by each gender.Results: Factors considered important by males and females across different levels of habitual intake include personal knowledge about dairy products and misconceptions regarding dairy foods and their associated health benefits; food characteristics, including taste; personal behaviors such as habits or routines including dairy products; social environments including parental and peer influence; physical environments factors such as availability and skipping meals; and the convenience of dairy products. Interestingly, only males noted sports as a positive influence for dairy product intake. Also, there were differences in the way males and females perceived dining out as affecting their dairy intake.Conclusion: Results suggest several potential factors that nutrition education interventions aiming to increase dairy consumption could target.